Oxygen isotope ratios of sedimentary biogenic silica reflect the European transcontinental climate gradient - Tyler, J; Leng, M; Sloane, H; Sachse, D; Gleixner, G (2008)
Oxygen isotope ratios of biogenic silica offer considerable potential in tracing past climate change using both marine and lacustrine sediment records. Despite recent improvements and standardisation in preparatory and analytical methods, evidence for a systematic relationship between climate parameters and the oxygen isotope composition of sedimentary diatom silica (δ18Osilica) is contradictory. In particular, observed differences between the δ18Osilica of living and sedimentary diatom silica in both lake and marine environments question the validity of applying isotope fractionation models derived from living diatoms to reconstructing climate from sediment records. In order to address this issue, oxygen isotope ratios of biogenic silica (δ18Osilica) are examined from a suite of lake surface sediment samples which span a large climatic gradient across western Europe. δ18Osilica values are strongly correlated with air temperature and the isotope composition of precipitation (δ18Op). When evaporation of lake waters is accounted for, the time-averaged surface sediment data suggest a fractionation of ∼35‰ between water and biogenic silica. However, the effect of temperature appears less marked than that observed between contemporary diatoms and lake water over short timescales, suggesting that diagenetic processes may lead to a reduction in the temperature sensitivity of sediment δ18Osilica records. Comparison of δ18Osilica data with δD analysed from n-alkanes of aquatic origin (n-C17, n-C21 and n-C23) demonstrates that the slope of the regional δ18O:δD water line is preserved within the sediment record, offering exciting potential for palaeoclimate research. © Natural Environment Research Council (NERC) copyright 2008. Reproduced with the permission of NERC. Published by John Wiley and Sons, Ltd.